ANALISIS MARKETING MIX PADA PRODUK KAIN TENUN MASRAIS DI KOTA BIMA - Sri Ernawati; Ita Tri Purnamasari; Gunawan Sakti (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2024)
This research aims to determine the marketing mix for masrais woven fabric products in Bima City. The type of research used is descriptive, research location in Bima City. The population in this study were all consumers who had purchased masrais weaving products. The sample in this study was 100 people using a purposive sampling technique. The research instrument uses a questionnaire with Likert scale measurements. The type of data used in this research is quantitative data with the research data source being primary data. Data collection techniques are observation, questionnaires/questionnaires and literature study. Data analysis used a one sample t test. The research results show that the marketing mix for masrais woven fabric products in Bima City is above the predetermined criteria of 75% (Good)